Construction Safety Management System Implementation Model Based on Minister of Public Works and Public Housing Regulation Number 10 of 2021 to Support Infrastructure Development in East Java Province - Ery Farida; Qomariyatus Sholihah; Sri Andarini; M. Halim Natsir (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to develop a model for implementing a Construction Safety Management System (CSMS) in accordance with Minister of Public Works and Public Housing Regulation Number 10 of 2021, tailored to support infrastructure development in East Java Province. Employing a qualitative research approach with a phenomenological lens, the interpretative phenomenological analysis yielded four key themes and thirteen associated insights. These include a detailed breakdown of the SMKK document, the scope of integrated construction work, special work considerations, and safety guarantees for buildings and construction assets. Noteworthy findings encompass the comprehensive structure of the SMKK document, the regulatory landscape shaping integrated construction, criteria for special work, and the roles of infrastructure operators and project organizers in ensuring construction safety.